Does location matter for firm R&D behaviour Some empirical evidence - Anni Lene Broberg (European Regional Science Association (ERSA), 2001)
Taking inspiration from KLEINKNECHT and POOTs (1992) survey this paper examine whether regional location matters for Danish firms' R&D performance. The urban hierarchy hypothesis is examined on the micro dataset obtained by merging Danish R&D statistics with account data. Both the logit analysis on the probability of firms undertaking R&D and tobit analysis on R&D intensities reveals that the R&D performances of firms located in urban agglomerations are greater than for firms elsewhere. Other non-regional factors such as ownership (dependence), industry and age are as well estimated to have a significant influence on firms' R&D performance. In addition, the firm's size and market share respectively has a significant affect on the probability of firms undertaking R&D and R&D intensity. However, comparing non-regional with regional dummies, the non-regional dummy variables seem to be of more importance.
Keywords: 330